2008
DOI: 10.1111/j.1468-2451.2009.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Support for multiculturalism in The Netherlands

Abstract: A study on the support for multiculturalism was carried out among 250 members of the majority group in a Dutch city. The concept of multiculturalism was found to be one‐dimensional. The e2nd2orsement of multiculturalism was moderate and varied across domains; the respondents were neutral towards the (dis)approval of cultural diversity and the acculturation strategies of majority group members, positive towards equal societal participation and interaction between majority group members and immigrants, and negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…There seems to be a widely held view, stimulated by the Dutch public media, which holds that support of multiculturalism has decreased remarkably following these negative events. A comparison of data collected prior to 9/11 (Arends‐Tóth & Van de Vijver, 2003), between 9/11 and the assassination of Fortuyn (the current study), and after the latter event (Schalk‐Soekar, Breugelmans, & Van de Vijver, in press) shows a remarkable stability in the neutral attitude of the Dutch majority. So, multicultural attitudes seem to be stable in The Netherlands, even after seemingly crucial, negative events.…”
Section: Discussionmentioning
confidence: 65%
“…There seems to be a widely held view, stimulated by the Dutch public media, which holds that support of multiculturalism has decreased remarkably following these negative events. A comparison of data collected prior to 9/11 (Arends‐Tóth & Van de Vijver, 2003), between 9/11 and the assassination of Fortuyn (the current study), and after the latter event (Schalk‐Soekar, Breugelmans, & Van de Vijver, in press) shows a remarkable stability in the neutral attitude of the Dutch majority. So, multicultural attitudes seem to be stable in The Netherlands, even after seemingly crucial, negative events.…”
Section: Discussionmentioning
confidence: 65%
“…The scale was developed on the basis of the Multicultural Ideology Scale by Berry and Kalin (1995). The MAS (Breugelmans & Van de Vijver, 2004; Schalk‐Soekar, Breugelmans, & Van de Vijver, in press) and adaptations of the MAS (Schalk‐Soekar & Van de Vijver, in press) have repeatedly shown excellent psychometric properties. Similar to applications of the Multicultural Ideology Scale in the Netherlands (Arends‐Tóth & Van de Vijver, 2003), the scale is unidimensional and has a high internal consistency.…”
Section: Methodsmentioning
confidence: 99%
“…Although the four domains do not represent separate factors—they all pertain to the single construct of multiculturalism—mean endorsement rates differ across domains. People tend to be the most positive about multiculturalism in the domain of Equal Rights and Social Participation and least positive in the domain of Acculturation by Minorities (Breugelmans & Van de Vijver, 2004; Schalk‐Soekar et al., in press).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arends-Tôth and van de Vijver (2003) found that immigrants viewed integration as the preferred mode of acculturation in their public domain (e.g., work context), but that separation was preferred in the private domain (e.g., spare time). From the perspective of majority members, however, Schalk-Soekar, Breugelmans, and van de Vijver (2008) found that majority members believed it was impossible for immigrants to combine minority culture maintenance and adjustment to the majority society, implying that maintaining one culture automatically means letting go of the other.…”
Section: Immigrants' Cultural Identity and Acculturation Strategiesmentioning
confidence: 99%